Salvage of Recurrence after Surgery and Adjuvant Therapy: A Multi-institutional Study. (July 2019) - Zenga, Joseph; Graboyes, Evan; Janz, Tyler; Drake, Virgina; Rettig, Eleni; Desai, Shaun; Nickel, Christopher; Shabani, Sepehr; Padhya, Tapan; Scarpinato, Mario; Stadler, Michael; Massey, Becky; et al.
Objectives: To determine the oncologic outcomes of patients undergoing salvage surgery for recurrent oral cavity squamous cell carcinoma (OCSCC) and oropharyngeal squamous cell carcinoma (OPSCC) after initial treatment with surgery and adjuvant therapy. Study Design: Retrospective case series with chart review. Setting: Five academic tertiary care centers. Subjects and Methods: Patients included those with OCSCC and OPSCC who were initially treated with surgery and adjuvant therapy between 2000 and 2015 and underwent salvage surgery for local and/or regional recurrence. Results: A total of 102 patients were included (76% OCSCC, 24% OPSCC). Five-year overall survival was 31% (95% CI, 21%-41%) and was significantly improved among patients with human papillomavirus–associated oropharyngeal tumors (hazard ratio [HR], 0.34; 95% CI, 0.11-0.98) and significantly worse for those with postoperative positive margins (HR, 2.65; 95% CI, 1.43-4.93). Adjuvant (chemo)reirradiation was not associated with disease control or survival regardless of margin status. Combined locoregional recurrence was significantly correlated with a positive margin resection (HR, 5.75; 95% CI, 1.94-17.01). Twenty-five patients (25%) underwent a second salvage surgical procedure, of whom 8 achieved long-term disease control. Conclusion: Patients presenting with resectable recurrence after initial therapy with surgery and adjuvant therapy have a reasonable salvage rate when a negative margin resection can be attained. Patients with postoperative positive margins have poor survival outcomes that are not significantly improved with adjuvant (chemo)reirradiation. Those with combined locoregional recurrence are at particularly high risk for postoperative positive margins. The functional consequences of salvage surgery and its effect on quality of life are critical in decision making and require further investigation.